A new approach to Spectral Domain Method: Functional programming - Balik, Hasan H.; Sevinc, Bahadir; Akbal, Ayhan (Springer-Verlag Berlin, 2006)
The Spectral Domain Method is powerful technique to analyze planar microwave circuits. But available conventional programming languages used in the literature does not give the enough speed to use the Spectral Domain Method to develop package analysis program. Functional approach to Spectral domain Method gives a high level of programming and a variety of features which help to build elegant yet powerfully and general libraries of functions.
6th International Conference on Computational Science (ICCS 2006) -- MAY 28-31, 2006 -- Reading, ENGLAND
Keywords: Microstrip Circuits; Time-Domain